ANALYSIS OF THE FACTORS CAUSING PROCRASTINATION IN THE PREPARATION OF THESISFOR EDUCATION STUDENTS STATE UNIVERSITY SOCIETY MEDAN - Amelia, Dita Nurva; Kurniawan, Fauzi (Jurnal Empowerment, 2025)
This study discusses the factors that cause procrastination in the preparation of theses for students majoring in public education at Medan State University. This research was conducted using a descriptive approach with quantitative methods. The purpose of this research is to analyze the factors that cause procrastination in the preparation of thesis for students majoring in public education at Medan State University. The sample in this study included 41 students majoring in Community Education from the 2016-1019 class. The research results were influenced by two factors, namely internal and external factors. From these two factors, it was found that the factor that most influences the occurrence of procrastination in the preparation of a thesis is the internal factor with a value of 46%. This means that student procrastination is caused by the student's physical condition, such as the desire to graduate on time, make improvements after the thesis guidance process, and ease of accessing theories or journals related to the thesis. The causes of procrastination are also influenced by the student's psychological condition, such as having knowledge of standard and scientific vocabulary, being able to express the right thoughts and ideas in completing the thesis, having a clear schedule and being able to make the best possible time to complete the thesis.